(untitled) (Physical Education, Health and Social Sciences, 2025)
The study was carried out to explore the fauna od beetles (Coleoptera) at district Charsadda, Khyber Pakhtunkhwa, Pakistan. Total 170 specimens were collected by using hand net and were identified with the help of available literature. Among the collected specimens, 3 genera via Cyclocephala, Entomoscelis and Limodromus were reported as new to the fauna of Pakistan. Diagnostic characters of the genera along with digital images were also provided.